Study of ascorbic acid priming on germination and biochemical indexes of sheep fescue (Festuca ovina) seeds under drought stress - Hossein Reza Rouhi; mohammad hasan vafaei; Maryam Saman; Alireza Shahbodaghlo (علوم و فناوری بذر ایران, 2021)
Germination of seeds, one of the most critical stages of plant cycle is greatly influenced by drought stress. In this way, the effects of ascorbic acid to improve germination and antioxidant enzyme activities in sheep fescue seeds under drought stress were studied. A factorial experiment based on completely randomized design with three replications was done. None- primed seed (control group) and priming of different concentrations of ascorbic acid (0, 1 and 2 mM) under 0, -0.4, -0.8 and -1.2 MPa drought stress levels were evaluated. The results showed that seed priming with ascorbic acid in different drought levels increased some traits such as germination percentage, vigour index, plumule and radicle length, soluble carbohydrates and protein contents and antioxidant enzymes activities (catalase, superoxide dismutase and ascorbate peroxidase). While it decreased mean germination time, electrical conductivity and malondialdehyde content in comparison to nonprime seeds. So seed priming with 1 and 2 mM of ascorbic acid in -1.2 MPa level increased vigour index, soluble carbohydrates and proteins, respectively by 167.03, 22.26, 35.77, 187.91, 22.61 and 30.20% compared to nonprimed seeds. Also, it increased activity of catalase, superoxide dismutase and ascorbate peroxidase, respectively by 11.85, 22.81, 12.25, 13.83, 31.33 and 9.93% compared to non-primed seeds. Therefore, the use of 1 and 2 mM ascorbic acid concentrations to reduce the negative effects caused by drought stress is recommended.